(3GdCeKGds - (3CHh YHjO , GdbGSe Hf SdGe GdgQhj GdGROj GdNRGYj, CHh YHjO,J (B224 (3g` s
(3ChdgG (B:s
(3gPG cJGH GdGeKGd hgj Mce GdYQH ai GdLGgdjI hddGSdGe hHeG cGfJ GdYQH JYGQV cdGegG s
(3BNQgG (B:s
(3BNQ GdehLhO (B: (3HGH GdfSGHI ai ZjQ Phi GdGQMGe bGd GdGUeYi ef GeKGdge s
(3GdfSNI HgG MhGTs
(3HChdg ELGRI ef YHO GdLHGQ GdeYGaQi Edi CHj eMeO YHO GdHGbi Hf CHj GdaVd HQhGjI GdcJGH SfI (B551(3g` JfbU fMh GdKdKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B176 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B101s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ , JGeI s
Keywords: (3eJaQbGJs